The Toxoplasma gondii kinetochore is required for centrosome association with the centrocone (spindle pole). (10th September 2013) - Farrell, Megan; Gubbels, Marc‐Jan
Summary The kinetochore is a multi‐protein structure assembled on eukaryotic centromeres mediating chromosome attachment to spindle microtubules. Here we identified the kinetochore proteins Nuf2 and Ndc80 in the apicomplexan parasite Toxoplasma gondii. Localization revealed that kinetochores remain clustered throughout the cell cycle and colocalize with clustered centromeres at the centrocone, a structure containing the spindle pole embedded in the nuclear envelope. Pharmacological disruption of microtubules resulted in partial loss of some kinetochore and centromere clustering, indicating microtubules are necessary but not strictly required for kinetochore clustering. Generation of a TgNuf2 conditional knock‐down strain revealed it is essential for chromosome segregation, but dispensable for centromere clustering. The centromeres actually remained associated with the centrocone suggesting microtubule binding is not required for their interaction with the spindle pole. The most striking observation upon TgNuf2 depletion was that the centrosome behaved normally, but that it lost its association with the centrocone. This suggests that microtubules are essential to maintain contact between the centrosome and chromosomes, and this interaction is critical for the partitioning of the nuclei into the two daughter parasites. Finally, genetic complementation experiments with mutated TgNuf2 constructs highlighted an apicomplexan‐specific motif with a putative role in nuclear localization.